Implementation of BPHTB Exemption under Semarang Mayor Regulation No. 64/2024: Tlogosari Kulon Case Study (Indonesian Journal of Agrarian Law, 2026)
Socioeconomic inequality in the city of Semarang remains a fundamental issue, particularly regarding the limited access of low-income communities to land rights due to the fiscal burden of the Land and Building Acquisition Tax (BPHTB). This study aims to analyze the implementation of Semarang Mayor Regulation No. 64 of 2024 on the Exemption from the Land and Building Acquisition Tax for Low-Income Communities through a case study in the Tlogosari Kulon Subdistrict, Semarang City, from the perspective of John Rawls’s social justice theory, particularly in guaranteeing the rights of the least advantaged through the mechanism of fairness. The research method used was an empirical legal approach with a case study design, involving in-depth interviews with representatives from Bapenda, Disperkim, Distaru, village officials, and residents categorized as low-income individuals, utilizing qualitative document analysis. The research results indicate a significant implementation gap, characterized by ineffective inter-agency coordination and a digital e-BPHTB infrastructure that remains unintegrated for the automatic verification of MBR status. Administrative complexities and a lack of outreach at the sub-district level have led to administrative exclusion of eligible residents. Without substantive integration between legal norms and technical systems, this policy remains merely formalistic and has yet to yield transformative impacts on social justice. Research recommendations include integrating the e-BPHTB platform with the Integrated Social Welfare Data (DTKS), strengthening the role of sub-districts as administrative facilitators, and synchronizing the exemption policy with the Comprehensive Systematic Land Registration (PTSL) program.